Complete Genome Sequence of a Thermophilic Hydrogenotrophic Methanogen, Methanothermobacter sp. Strain CaT2 - Kosaka, Tomoyuki (American Society for Microbiology, 2013)
We isolated a thermophilic hydrogenotrophic methanogen, Methanothermobacter sp. strain CaT2, which is able to aggregate and utilize formate. Here, we report the complete genome sequence of this organism.